The Role of Intestinal Permeability in Gastrointestinal Disorders and Current Methods of Evaluation - Vanuytsel, Tim; Tack, Jan; Farre, Ricard (Frontiers in Nutrition, 2021)
An increased intestinal permeability has been described in various gastrointestinal and non-gastrointestinal disorders. Nevertheless, the concept and definition of intestinal permeability is relatively broad and includes not only an altered paracellular route, regulated by tight junction proteins, but also the transcellular route involving membrane transporters and channels, and endocytic mechanisms. Paracellular intestinal permeability can be assessed in vivo by using different molecules ( e.g. sugars, polyethylene glycols, 51Cr-EDTA) and ex vivo in Ussing chambers combining electrophysiology and probes of different molecular sizes. The latter is still the gold standard technique for assessing the epithelial barrier function, whereas in vivo techniques, including putative blood biomarkers such as intestinal fatty acid-binding protein and zonulin, are broadly used despite limitations. In the second part of the review, the current evidence of the role of impaired barrier function in the pathophysiology of selected gastrointestinal and liver diseases is discussed. Celiac disease is one of the conditions with the best evidence for impaired barrier function playing a crucial role with zonulin as its proposed regulator. Increased permeability is clearly present in inflammatory bowel disease, but the question of whether this is a primary event or a consequence of inflammation remains unsolved. The gut-liver axis with a crucial role in impaired intestinal barrier function is increasingly recognized in chronic alcoholic and metabolic liver disease. Finally, the current evidence does not support an important role for increased permeability in bile acid diarrhea.